Corporate Governance And Firm Performance Before And After Financial Crisis 2006-2013: An Analysis Of Financial Sector In Malaysia - Wan Yusoff, Wan Fauziah (Archives of Business Research, 2015)
Corporate governance is one of the important determinants to improve the accountability of the company and enhance business prosperity. Hence good corporate governance has been major of concerned by investors to build up trust towards the company. In contrary, poor corporate governance frameworks in a firm faced the problem of lack of investor’s confidence and failed to perform well in the achievements. This research aims to investigate the relationship between corporate governance and firm performance before and after the financial crisis for year 2006-2013 of the financial sector in Malaysia. The independent variables used in this study were independent directors, board size and CEO duality. While two dependent variables were chosen; earnings per share (EPS) and return on assets (ROA). Data was collected from the company’s annual reports for the year 2006 and year 2013. This study revealed that the independent directors and CEO duality have not influence firm performance before and after financial crisis (2006-2013). However, board size found to have negative relationship with financial performance for both years. It can be concluded that there is no relationship between corporate governance before and after financial crisis. Corporate governance plays an important role regardless especially during the economic downturn.